Designing Biology Learning Media to Increase Student Interest using Design Thinking Method - Uraefatul Jannah; Ayu Qonita; Mutia Nurul Ilmi; Ira Firanda Gumita; Yustitia K. Zaenudin; Rita Lefrida (IKIP Mataram, 2024)
Media is one of the components in learning that has a function as a means of non-verbal communication. In designing instructional media, a teacher needs to adapt to the students need. As a result, it can be effective and efficient. Students as learning centers are expected to develop and have better communication skills, so that they can participate actively, be able to analyze and be able to solve their own problems. Learning media that attracts students' interest will create creativity and innovation to themself which is in line with the challenges of the twenty-first century. On the other hand, the mindset that can bring out the creative potential in everyone is Design Thinking. In this research, we use a theoretical perspective from design thinking with activities that consist of 5 stages, namely empathize, define, ideate, prototype, and test. We conducted in-depth observations and interviews to identify problems in students of class X-4 at the Madani Integrated Model Senior High School. The sample used was 4 students. The sample selection was based on the extreme right and left extreme sample criteria. The findings in the interview formed an